Study on the complex relationship of tourism-economy-ecological environment in arid zones: the case of Xinjiang, China - Liu, Haijun; Chen, Beizi; Xia, Qianqian; Zabi, Gulnigar; Li, Gaofeng (Frontiers in Environmental Science, 2024)
The synergistic integration of tourism, the economy, and the ecological environment within a region is crucial for promoting its sustainable development. Tourism acts as a catalyst for green economic growth, yet varying levels of tourism development can intensify the strain on the ecological environment. Thus, achieving a Pareto optimal balance among the benefits of these three entities holds significant theoretical and practical relevance. This research utilizes statistical data spanning from 2000 to 2021 to devise a tourism-economyecological environment (TEE) indicator system for Xinjiang. The study employs a coupled coordination model to analyze the spatial and temporal coupling dynamics between subsystems and to classify the types of coupled coordination. The analysis also identifies obstacles that impede the degree of coordination. The findings indicate that during the period under investigation, the TEE system in Xinjiang experienced consistent growth. However, the tourism subsystem exhibited disparate development and pronounced resource monopolization, which stimulated the economic subsystem's growth, albeit with noticeable developmental lags in the latter stages. Spatially, economic performance demonstrated a declining trend from core urban centers like Urumqi City and Karamay City towards peripheral areas. From an ecological perspective, the distribution of resources exhibited a heterogeneous "M-V-W" pattern, characterized by significant disparities in the availability of natural resources and the occurrence of localized ecological deterioration. There is a notable and increasing degree of coupled coordination in regional synergistic development, which is primarily manifested in the delayed development of tourism. The combined development of the three subsystems is influenced by some factors, including environmental pollution, resources, economic quality, and industrial structure. Soot emissions, green space per capita in parks, and sulfur dioxide emissions are identified as key constraints. This study provides theoretical backing and empirical evidence for economic growth, the optimization of industrial structure, and the preservation of the ecological environment in arid and semi-arid regions globally.